Metasomatic effect of Li-bearing aplite-pegmatites on psammitic and pelitic metasediments: Geochemical constraints on critical raw material exploration at the Fregeneda-Almendra Pegmatite Field (Spain and Portugal) - Errandonea-Martin, J (2022)
Fluid-assisted mass transfer and re-equilibration of mineral phases are common consequences of metasomatism associated with igneous intrusions. The addition and/or removal of chemical components in these environments may result in the generation of metasomatic aureoles, which can be recognized by their mineralogy and geochemistry. Due to an increasing demand for critical raw materials used in green energy technologies, rare-element granitic pegmatites have seen renewed interest in the mineral exploration industry. Granitic pegma-tites represent potential sources of critical commodities and geochemical studies of their related aureoles help to advance techniques in exploration targeting. Moreover, the role and timing of fluid exsolution during magma-tic-hydrothermal evolution in granitic-pegmatitic systems and concomitant element mobility remain highly debated.We present a prospect-scale systematic study of geochemical haloes generated by LCT (Li-Cs-Ta) family pegmatite dykes from the Fregeneda-Almendra Pegmatite Field, in the Central Iberian Zone of the Iberian Massif (Spain and Portugal). To understand the magnitude of metasomatic processes linked to these intrusions, we performed whole-rock mass-balance calculation of element gains and losses in variably metasomatized psam-mitic and pelitic host metasediments. The results show that F, B, Li, Rb, Cs, Sn, Be, Tl, As, W and S (+/- Mo, Ta) were carried by early exsolved and expelled aqueous fluids. The first evidence of element enrichment is recorded at distances of 4-5 times the thickness of the dykes, with exponentially increasing gains of those fluid-mobile elements proximal to the pegmatite margin. Enrichments that were detected farthest from the pegmatite mar-gins were those of Li and Cs, followed by Rb and, to a lesser extent, Sn, F, B, Be, and Tl. The most evolved (fractionated) aplite-pegmatites generated the broadest haloes, with concentrations higher than 200 ppm Li, 30 ppm Cs, 300 ppm Rb, and 15 ppm Sn in the metasediments indicating proximity to a mineralized dyke. In addition, absolute gains of up to-4000 ppm Li,-1300 ppm Cs,-1300 ppm Rb, and 170 ppm Sn in the host rocks could point to the presence of superimposed haloes from multiple evolved dykes.